Remarks concerning several newly published military inscriptions on instrumentum - Peter Rothenhöfer (Gephyra, 2017)
A recently published inscription on a Roman measure (Gephyra 13, 2016, 119-125) mentioning a sextarium exsaciatum prompted Hugo Beikircher to suggest a different understanding of the hitherto unknown word exsaciatum, proposing a connection to the verb exsatiare instead of deriving it from exactus.